U.S. Food and Drug Administration Approval Summary: Ramucirumab for the Treatment of Metastatic Non‐Small Cell Lung Cancer Following Disease Progression On or After Platinum‐Based Chemotherapy. (7th October 2015) - Larkins, Erin; Scepura, Barbara; Blumenthal, Gideon M.; Bloomquist, Erik; Tang, Shenghui; Biable, Missiratch; Kluetz, Paul; Keegan, Patricia; Pazdur, Richard
Abstract : On December 12, 2014, the U.S. Food and Drug Administration (FDA) approved ramucirumab for use in combination with docetaxel for the treatment of patients with metastatic non‐small cell lung cancer (NSCLC) with disease progression on or after platinum‐based chemotherapy. Patients with epidermal growth factor receptor or anaplastic lymphoma kinase genomic tumor aberrations should have disease progression on FDA‐approved therapy for these aberrations prior to receiving ramucirumab. This approval was based on an improvement in overall survival (OS) with an acceptable toxicity profile in a randomized, multicenter, double‐blinded, placebo‐controlled trial of 1, 253 patients with metastatic NSCLC previously treated with a platinum‐based combination therapy. Patients were randomized 1:1 to receive either ramucirumab in combination with docetaxel or placebo in combination with docetaxel. The primary endpoint was OS. Patients who received ramucirumab in combination with docetaxel had improved OS (hazard ratio [HR]: 0.86; 95% confidence interval [CI]: 0.75, 0.98). Median OS was 10.5 months on the ramucirumab plus docetaxel arm versus 9.1 months on the placebo plus docetaxel arm. The most frequent (≥30%) adverse reactions in ramucirumab‐treated patients were fatigue, neutropenia, and diarrhea. The most frequent (≥5%) grade 3 and 4 adverse reactions in the ramucirumab arm were fatigue, neutropenia, febrile neutropenia, leukopenia, and hypertension. Implications for Practice: This report presents key information on the U.S. Food and Drug Administration approval of ramucirumab, a monoclonal antibody targeting vascular endothelial growth factor receptor‐2, given in combination with docetaxel for the treatment of patients with metastatic non‐small cell lung cancer whose disease has progressed on or after platinum‐based chemotherapy. This report specifically addresses the issues of safety in patients with squamous cell tumors, effect of treatment in elderly patients, and uncertainties regarding effects in patients with tumors harboring epidermal growth factor receptor or anaplastic lymphoma kinase genomic tumor aberrations. Abstract : Ramucirumab is approved by the U.S. Food and Drug Administration for use with docetaxel for the treatment of patients with metastatic non‐small cell lung cancer with disease progression on or after platinum‐based chemotherapy. The approval was based on improved overall survival (median, 10.5 months) with an acceptable toxicity profile in a randomized, multicenter, double‐blinded, placebo‐controlled trial of 1, 253 patients. The most frequent (≥30%) adverse reactions were fatigue, neutropenia, and diarrhea.